Intestinal B cells license metabolic T-cell activation in NASH microbiota/antigen-independently and contribute to fibrosis by IgA-FcR signalling - Kotsiliti, Elena; Leone, Valentina; Schühle, Svenja; Govaere, Olivier; Li, Hai; Wolf, Monika J.; Horvatic, Helena; Bierwirth, Sandra; Hundertmark, Jana; Inverso, Donato; Zizmare, Laimdota; Sarusi-Portuguez, Avital; et al. (Journal of hepatology, 2023)
Background & Aims - The progression of non-alcoholic steatohepatitis (NASH) to fibrosis and hepatocellular carcinoma (HCC) is aggravated by auto-aggressive T cells. The gut-liver axis contributes to NASH, but the mechanisms involved and the consequences for NASH-induced fibrosis and liver cancer remain unknown. We investigated the role of gastrointestinal B cells in the development of NASH, fibrosis and NASH-induced HCC. - Methods - C57BL/6J wild-type (WT), B cell-deficient and different immunoglobulin-deficient or transgenic mice were fed distinct NASH-inducing diets or standard chow for 6 or 12 months, whereafter NASH, fibrosis, and NASH-induced HCC were assessed and analysed. Specific pathogen-free/germ-free WT and μMT mice (containing B cells only in the gastrointestinal tract) were fed a choline-deficient high-fat diet, and treated with an anti-CD20 antibody, whereafter NASH and fibrosis were assessed. Tissue biopsy samples from patients with simple steatosis, NASH and cirrhosis were analysed to correlate the secretion of immunoglobulins to clinicopathological features. Flow cytometry, immunohistochemistry and single-cell RNA-sequencing analysis were performed in liver and gastrointestinal tissue to characterise immune cells in mice and humans. - Results - Activated intestinal B cells were increased in mouse and human NASH samples and licensed metabolic T-cell activation to induce NASH independently of antigen specificity and gut microbiota. Genetic or therapeutic depletion of systemic or gastrointestinal B cells prevented or reverted NASH and liver fibrosis. IgA secretion was necessary for fibrosis induction by activating CD11b+CCR2+F4/80+CD11c-FCGR1+ hepatic myeloid cells through an IgA-FcR signalling axis. Similarly, patients with NASH had increased numbers of activated intestinal B cells; additionally, we observed a positive correlation between IgA levels and activated FcRg+ hepatic myeloid cells, as well the extent of liver fibrosis. - Conclusions - Intestinal B cells and the IgA-FcR signalling axis represent potential therapeutic targets for the treatment of NASH. - Impact and Implications - There is currently no effective treatment for non-alcoholic steatohepatitis (NASH), which is associated with a substantial healthcare burden and is a growing risk factor for hepatocellular carcinoma (HCC). We have previously shown that NASH is an auto-aggressive condition aggravated, amongst others, by T cells. Therefore, we hypothesized that B cells might have a role in disease induction and progression. Our present work highlights that B cells have a dual role in NASH pathogenesis, being implicated in the activation of auto-aggressive T cells and the development of fibrosis via activation of monocyte-derived macrophages by secreted immunoglobulins (e.g., IgA). Furthermore, we show that the absence of B cells prevented HCC development. B cell-intrinsic signalling pathways, secreted immunoglobulins, and interactions of B cells with other immune cells are potential targets for combinatorial NASH therapies against inflammation and fibrosis.
Online verfügbar: 22. Mai 2023, Artikelversion: 14. Juli 2023
Gesehen am 12.10.2023